2010
DOI: 10.1038/ng.557
|View full text |Cite
|
Sign up to set email alerts
|

From transcriptome analysis to therapeutic anti-CD40L treatment in the SOD1 model of amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive loss of motor neurons. Using unbiased transcript profiling in an ALS mouse model, we identified a role for the co-stimulatory pathway, a key regulator of immune responses. Furthermore, we observed that this pathway is upregulated in the blood of 56% of human patients with ALS. A therapy using a monoclonal antibody to CD40L was developed that slows weight loss, delays paralysis and extends survival in an ALS mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 39 publications
5
76
0
1
Order By: Relevance
“…There is also potential indication that NOX1 deficiency might slow the course of the ALS mouse model (118). One pharmacological study using the antioxidant/NOX inhibitor apocynin suggested a strong increase in the survival of ALS mice (68); however, this was not confirmed by other studies (110,170).…”
Section: Studies In Humansmentioning
confidence: 68%
“…There is also potential indication that NOX1 deficiency might slow the course of the ALS mouse model (118). One pharmacological study using the antioxidant/NOX inhibitor apocynin suggested a strong increase in the survival of ALS mice (68); however, this was not confirmed by other studies (110,170).…”
Section: Studies In Humansmentioning
confidence: 68%
“…Our investigations found perivascular and intraparenchymal CD4 + T lymphocytes in the proximity of degenerating corticospinal tracts and ventral horns in two-thirds of ALS patients (11). In the blood of patients with ALS, alterations in T lymphocyte populations have also been described as compared with controls (12)(13)(14)(15)(16); however, these studies do not address whether T lymphocytes directly or indirectly influence disease progression.…”
Section: Introductionmentioning
confidence: 74%
“…Although ALS is not primarily considered an inflammatory or immune-mediated disease, immune mechanisms appear to play a role in pathogenesis of the disease. In both ALS patients and animal models, inflammatory responses are observed (2)(3)(4)(5)(6)(7)(8). Furthermore, non-neuronal cells such as microglia (9) and astrocytes (10) are activated during disease progression, and evidence suggests that they contribute to neuronal death.…”
Section: Introductionmentioning
confidence: 99%